Effects of low oxygen concentrations and metabolic inhibitors on proteoglycan and protein synthesis rates in the intervertebral disc. - Ishihara, H; Urban, J (J Bone Jt Surgery Inc., 1999)
The intervertebral disc is the largest asvacular structure in the body; consequently, there are steep gradients in O2 concentration, with PO2 falling to as low as 1% O2 in the centre of the disc. We investigated the effect of O2 concentration on the rates of O2 consumption, lactate production, and sulphate and proline incorporation in bovine caudal discs. We also investigated the effects of metabolic inhibitors of energy production pathways on tracer incorporation. Samples from the outer annulus and nucleus pulposus were incubated for 24 hours in 1-21% O2. Rates were measured during the last 4 hours of incubation. As O2 concentration was reduced from 10 to 1% O2, O2 consumption rates fell by around 75% and lactate production rates almost doubled; the bovine discs thus showed a positive progressive Pasteur effect. Incorporation rates of [3H]proline and [35S]sulphate were lowest at 1% O2. In the nucleus, but not in the outer annulus, the rate of [35S]incorporation peaked at 5% O2, where it was 30% greater than at 21% O2 and 150% greater than at 1% O2. The competitive glycolysis inhibitor 2-deoxyglucose, the oxidative phosphorylation uncoupler 2,4-dinitrophenol, and the oxidative phosphorylation inhibitor sodium azide all markedly reduced sulphate incorporation. These results, together with previous measurements of CO2 production rates, suggest that a functionally significant fraction of the disc's energy is supplied by oxidative phosphorylation. However, low levels of PO2, 2,4-dinitrophenol, and sodium azide have been reported to reduce sulphate incorporation in articular cartilage, a tissue that derives its energy almost entirely from glycolysis.